The Effect of Sports Education on Adolescent Self-Esteem (A Comparative Study Between Students in Special Sports Classes and Regular Classes) - Sabarini, Sri Santoso; Darlina; Shidiq, Abdul Aziz Purnomo (LPPM Undiksha, 2023)
Identity crises are common in adolescence, which can lead to destructive behavior. Sport affects behavior indirectly through positive competitive attitudes and negative stereotypical destructive behavior. This study analyzes sports education on self-esteem in special and regular sports education. This type of research is quantitative, with an ex post facto approach. The subjects in the study were 200 respondents consisting of special sports class (KKO) students, regular class students, and parents/guardians of ninth-grade junior high school students. The data collection technique used a self-esteem questionnaire from the Rosenberg Self-Esteem Scale (RSES). Test the instrument's validity with Pearson's product-moment correlation coefficient, while the instrument reliability test uses Cronbach's Alpha technique. The data analysis technique used is a one-way ANOVA test. The results showed that there were differences between KKO and regular students. Student participation, especially adolescents at the junior high school (SMP) level in sports activities, has a high level of tendency. The existence of special sports classes (KKO) whose curriculum is designed systematically and structured to implement sports training programs and harmonious general education has a psychological effect on adolescent students. Thus, it can be concluded that there is an effect of sports education on self-esteem in KKO students. This research implies that sports education that is managed properly has a positive impact on adolescents.